Sympathetic Nervous System Control of Carbon Tetrachloride-Induced Oxidative Stress in Liver through α-Adrenergic Signaling. (21st December 2015) - Lin, Jung-Chun; Peng, Yi-Jen; Wang, Shih-Yu; Lai, Mei-Ju; Young, Ton-Ho; Salter, Donald M.; Lee, Herng-Sheng
Abstract : In addition to being the primary organ involved in redox cycling, the liver is one of the most highly innervated tissues in mammals. The interaction between hepatocytes and sympathetic, parasympathetic, and peptidergic nerve fibers through a variety of neurotransmitters and signaling pathways is recognized as being important in the regulation of hepatocyte function, liver regeneration, and hepatic fibrosis. However, less is known regarding the role of the sympathetic nervous system (SNS) in modulating the hepatic response to oxidative stress. Our aim was to investigate the role of the SNS in healthy and oxidatively stressed liver parenchyma. Mice treated with 6-hydroxydopamine hydrobromide were used to realize chemical sympathectomy. Carbon tetrachloride (CCl4 ) injection was used to induce oxidative liver injury. Sympathectomized animals were protected from CCl4 induced hepatic lipid peroxidation-mediated cytotoxicity and genotoxicity as assessed by 4-hydroxy-2-nonenal levels, morphological features of cell damage, and DNA oxidative damage. Furthermore, sympathectomy modulated hepatic inflammatory response induced by CCl4 -mediated lipid peroxidation. CCl4 induced lipid peroxidation and hepatotoxicity were suppressed by administration of an α -adrenergic antagonist. We conclude that the SNS provides a permissive microenvironment for hepatic oxidative stress indicating the possibility that targeting the hepatic α -adrenergic signaling could be a viable strategy for improving outcomes in patients with acute hepatic injury.